2006
DOI: 10.1161/circulationaha.105.570903
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and Cardiovascular Risk Across the Ankle-Arm Index Spectrum

Abstract: Background-A low ankle-arm index (AAI) is a strong predictor of mortality and cardiovascular events. A high AAI also appears to be associated with higher mortality risk in select populations. However, mortality and cardiovascular risk across the AAI spectrum have not been described in a more broadly defined population. Methods and Results-We examined total and cardiovascular mortality and cardiovascular events across the AAI spectrum among 5748 participants in the Cardiovascular Health Study (CHS). The mean ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
209
1
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 281 publications
(235 citation statements)
references
References 36 publications
19
209
1
6
Order By: Relevance
“…Using data from the Strong Heart Study 23) , they reported that the adjusted hazards ratio of ABI >1.4 was 1.77 (95%CI 1.48-2.13) for all-cause mortality and 2.08 (95%CI 1.49-2.94) for cardiovascular mortality. This association was confirmed by another cohort study [24][25][26] . It is suggested that high ABI could be related to poor arterial compressibility resulting from stiffness and calcification 26) .…”
Section: Resultssupporting
confidence: 59%
“…Using data from the Strong Heart Study 23) , they reported that the adjusted hazards ratio of ABI >1.4 was 1.77 (95%CI 1.48-2.13) for all-cause mortality and 2.08 (95%CI 1.49-2.94) for cardiovascular mortality. This association was confirmed by another cohort study [24][25][26] . It is suggested that high ABI could be related to poor arterial compressibility resulting from stiffness and calcification 26) .…”
Section: Resultssupporting
confidence: 59%
“…Previous studies in non‐CKD patients suggested that ABI of 0.9 to <1.0 predicted CVD and total mortality 6, 24. The American Heart Association (AHA) suggested that ABI should be interpreted according to the a priori probability of PAD, and values between 0.91 and 1.00 should be considered borderline 25.…”
Section: Discussionmentioning
confidence: 99%
“…a value lower than 0.9 is diagnostic of the disease, which is a synonym for high cardiovascular risk and mortality [4,34] PAD is an important predictor of cardiovascular morbidity and mortality [38], independent of age, sex and the presence of different CRF [39]. In this study the presence of PAD is signifi cantly associated with smoking, hypertension, DM, DL and obesity.…”
Section: Resultsmentioning
confidence: 63%